THE SOCIAL BACKGROUND OF BREXIT - Ahmed, Ahmed L.M. (Copernican Journal of Finance & Accounting, 2019)
The Brexit referendum will remain as a milestone in contemporary European history. The British exit from the EU is not going only to shape future relations between the EU and the UK, but it will shape the relation between Brussels and other member states as well. This study aims to investigate the main claims for the leave campaigns which affected the general opinion to vote for the exit. The two main points investigated in this paper are: first, the historical background regarding the UK and the EU, the reasons for the first refusal to the European integration projects during the 1950, and the changes in the British situation which pushed the UK to seek the membership for a decade before being able to join the EEC in the 1970s; and second, national identity, which affected Britain’s late entry to the EU, and shaped relations between London and Brussels during the British membership. The paper concludes that, unfortunately, British citizens in general were not aware of the full facts regarding the above two points.